Deciphering Heat Stress Mechanisms and Developing Mitigation Strategies in Dairy Cattle: A Multi-Omics Perspective - Zhiyi Xiong; Lin Li; Kehui Ouyang; Mingren Qu; Qinghua Qiu (Agriculture)
Heat stress (HS) in dairy cattle triggers systemic physiological disruptions, including milk yield decline, immune suppression, and reproductive dysfunction, jeopardizing sustainable livestock production. While conventional single-omics or phenotypic studies have provided fragmented insights, they fail to decipher the multi-layered regulatory networks and gene–environment interactions underlying HS. This review integrates current knowledge on HS-induced physiological responses and molecular adaptations in dairy cattle from a multi-omics perspective, highlighting integrative approaches that combine IoT-enabled monitoring and AI-driven genetic improvement strategies. However, key challenges persist, such as complexities in bioinformatic data integration, CRISPR off-target effects, and ethical controversies. Future directions will emphasize the development and application of AI-aided predictive models to enable precision breeding, thereby advancing climate-resilient genetic improvement in dairy cattle.